2021
DOI: 10.3390/su13126917
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Analysis of CFI Schemes with Different Length of Displaced Left-Turn Lanes with Entropy Method

Abstract: As an unconventional design to alleviate the conflict between left-turn and through vehicles, Continuous Flow Intersection (CFI) has obvious advantages in improving the sustainability of roadway. So far, the design manuals and guidelines for CFI are not enough sufficient, especially for the displaced left-turn lane length of CFI. And the results of existing research studies are not operational, making it difficult to put CFI into application. To address this issue, this paper presents a methodological procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…The calculation results of the MAPE are shown in Table 2. It can be seen that the total error between the VISSIM simulation model and the actual traffic is −2.7%, which indicates, as discussed in previous studies (Shao et al, 2019;Pan et al, 2021a;Pan et al, 2021b), that the proposed model meets the accuracy requirements of the actual project.…”
Section: Calibration Of the Simulation Modelsupporting
confidence: 62%
See 2 more Smart Citations
“…The calculation results of the MAPE are shown in Table 2. It can be seen that the total error between the VISSIM simulation model and the actual traffic is −2.7%, which indicates, as discussed in previous studies (Shao et al, 2019;Pan et al, 2021a;Pan et al, 2021b), that the proposed model meets the accuracy requirements of the actual project.…”
Section: Calibration Of the Simulation Modelsupporting
confidence: 62%
“…In order to ensure the simulation results' reliability, the model parameters were calibrated so that the outcomes were verified against the actual traffic parameters. This study follows the common model calibration procedure used in previous investigations (Shao et al, 2019;Pan et al, 2021a;Pan et al, 2021b) to calibrate the VISSIM simulation model using capacity indicators. The absolute percentage error (MAPE) between the measured capacity in each traffic direction at the intersection and the capacity in each direction in the simulation model is calculated, and the model is considered valid when the MAPE is less than 15%.…”
Section: Calibration Of the Simulation Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3 presents the calibration results of the VISSIM model across the four investigated LOS, where the diverging ratio is about 25%, with trucks accounting for 30% of the traffic. MAPE for both capacity and density remains at acceptable levels, as previous studies have confirmed that MAPE values under 15% can provide accurate and credible guidance for engineering practice [41,42]. Furthermore, to demonstrate the accuracy of the VISSIM model, various volumes were inputted, and the density results presented in Figure 12 align with the Greenshields model, exhibiting a 99% R 2 .…”
Section: Vissim Resultsmentioning
confidence: 54%
“…The entropy weighted method (EWM) is an objective, comprehensive evaluation method. Based on on-site survey data, we used VISSIM simulation [22][23][24] and the EWM [25][26][27] to calculate and evaluate the three schemes and selected the best scheme under different traffic volume combinations; we utilized VISSIM software to simulate various schemes. Ultimately, using the EWM, we conducted a comprehensive scoring of different schemes to determine the optimal construction organization method under varying traffic volumes.…”
Section: Introductionmentioning
confidence: 99%